Diana Wynne Jones’s Howl’s Moving Castle (1986) or the Story of a New Mythology - Yavaş, Seda (Journal of History Culture and Art Research, 2015)
Diana Wynne Jones’s Howl’s Moving Castle (1986) or The Story of a New Mythology Abstract This paper focuses upon Diana Wynne Jones’s 1986 fantasy novel Howl’s Moving Castle, part of the trilogy including Castle in the Air (1990) and House of Many Ways (2008). Taking place in a utopian land, the story creates a new mythology built upon magic, objects coming to life, no space boundaries and the search for eternal life and the perfect human. As a consequence, the paper will deal with the main elements of this mythology and the way in which they have been transposed in the 2006 Oscar-nominated movie version.